Exploring Studies on the Effect of Indirect Instruction on Student’s Achievement in Chemistry using Meta-Analytical Approach - Ngozi , M. Eya; Florence , O. Attah; Ijeoma , H.N. Nwoji (International Journal of Psychosocial Rehabilitation, 2024)
The trend of inconclusiveness in the studies on effect of indirect instructional methods/strategies onstudents’ achievement in chemistry necessitated this study. The purpose of the study was to integrate the resultsof the previous research studies on the effect of indirect instructional methods on students’ academicachievement in chemistry in Nigeria through a meta-analytic approach. Three research questions were posedand two hypotheses formulated to guide the study. The population of the study consisted of all previous researchreports on indirect instructional methods and students’ academic achievement in Nigeria between 1990 and2017. The sample consisted of published and unpublished Ph.D and master’s research reports on the effect ofindirect instructional methods on students’ academic achievement in chemistry between 1990-2017.Ttwentynine (29) Studies constituted the sample. The data collected were analysed using percentages statisticaltransformations and computation of Winer combined test. The results of the findings among others were thatthe mean effect size for all the 29 findings examined in effect of indirect instructional method on achievement inchemistry is 0.75 which represents a high effect size. Based on the findings, recommendations were made.